Perkembangan Teori Leadership: Transformational Leadhership dalam Perspektif Gender - Muwahidah Nur Hasanah (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2016)
Leadership theory is a theory that has been studied by many researchers and continues to experience developments to date. The development of this theory of leadership allows this theory to continue to be studied by incorporating other elements as its dimension. Tracking the development of leadership theory, transformational leadership as a theory that became the trend in the leadership of late, in this paper studied from the perspective of gender to find gender aspects of gender characteristics which are more represented by transformational leadership. based on a number of existing studies, it can be concluded that this transformational leadership contains female value so called by some researchers as feminime leadership style. Based on this it can be concluded that the theory of leadership studied with a gender perspective this led to a paradoxical reality, namely where the stereotype of women who at the beginning of the development of leadership theory into glass ceiling for women's career was found as a characteristic of transformational leadership which is currently a leadership style widely embraced because it is considered the most effective.Keywords: theory, Leadership, Gender